The Application of Android-based GeoGebra on Quadratic Equations Material toward Mathematical Creative Thinking ability - Septian, Ari; Sugiarni, Rani; Monariska, Erma (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
Students' low creative thinking skills and difficulty in drawing graphs from the given algebraic equations are the background of this study. The purpose of this study was to determine the mathematical creative thinking abilities between Android-based GeoGebra and ordinary learning. This study also investigated students’ responses to the application of Android-based GeoGebra. The research method used was quasi-experimental with a nonequivalent group pretest-posttest design. The instruments were a creative thinking test and a questionnaire. The subjects of this study were students of one of the junior high school in Cianjur selected by purposive sampling technique. The studied material was the quadratic equations as a part of algebra. The gain index data analysis technique used was the normality test and the Mann Whitney test while the questionnaire data responses were analyzed through the average percentage of students’ answers. As a result, the students' mathematical creative thinking ability with Android-based GeoGebra was better than ordinary learning. Also, the students provided positive responses to the application of Android-based GeoGebra.